Studies on the effective components of Actinidia macrosperma (Actinidiaceae) (I)——Analysis on the inorganic elements - LU Yin; CHEN Shao-yuan; WU Ping; Chan Gilbert; FU Cheng-xin (浙江大学学报. 农业与生命科学版)
This paper describes the semi-quantitative analysis of the inorganic elements needed for people's health that are present in the medicinal plant Actinidia macrosperma C. F. Liang by atomic emission spectrometry. The result will be useful for the further exploitation of this Chinese traditional medical resource.